Analysis of Fishermen's Basic Skills Training With A Computer-Based SECI Knowledge Management Approach - Darmawan, Daddy; Tahar, Mohd Mokhtar Hj; Erlani, Lalan (Universitas Negeri Semarang, 2023)
This study aims to explore an integrated framework that integrates SECI knowledge management, basic fishing techniques, diversity of ecological knowledge, innovation abilities, fisherman's performance. The research design uses descriptive quantitative research, and the research methodology uses survey research with 150 respondents with purposive sampling in Kupang district, West Nusa Tenggara, which forms the target population. Statistical techniques use confirmatory factor analysis and structural equation modeling (SEM) using SmartPLS4 to test hypotheses. The test revealed a significant increase in the overall score of the trainees and skills. The specific score for the X2 table value was 149.334 compared to the calculated X2 value of 944.501, so the form of this model can be said to be FIT because X2 count X2 table. Furthermore, the value of Adjusted R Square gives a more substantial picture than R Square in assessing the ability of an exogenous construct to explain endogenous constructs, namely BFT_0.788, DEK_0.815, FP_0.636 and IA_0.725. Furthermore, the path coefficient values in this study are FP_ - IA_0.852, IA_ - BFT_0.324, IA_ - DEK_0.525, SKM_ - BFT_ 0.605, SKM_ - DEK_0.423 and SKM_- FP_0.798. From these tests, only BFT and DEK were seen to be less than 0.5. The results show that process knowledge management affects several observational variables, namely organizational knowledge, information management affects the nautical ability, process knowledge management involves Fishing basic techniques, Diversity of ecological expertise, maritime learning through mediators, Information management, and organizational knowledge. Therefore, the application of computer-based SECI knowledge management in this study is said to be significant.